2022
DOI: 10.1590/0034-7167-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and adherence to the pharmacological treatment by people with arterial hypertension

Abstract: Objective: To analyze the association between health literacy and the adherence to the pharmacological treatment of Brazilians with arterial hypertension. Methods: Cross-sectional study with 234 participants who responded an on-line sociodemographic and clinical characterization questionnaire, in addition to evaluation of health literacy and of the adherence to their pharmacological treatment. Data were analyzed using descriptive statistics and difference and correlation tests. Results: People with post-grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…The results of this study demonstrated that adherence to medication had a significant relationship with illness perception and all HL dimensions. This result is in line with previous studies which reported the strong association between medication adherence and health literacy among older adults hypertensive patients ( 36 ) and people with hypertension ( 25 , 37 ). Baharvand et al ( 38 ) found that perceptions of illness consequences could significantly predict treatment adherence.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study demonstrated that adherence to medication had a significant relationship with illness perception and all HL dimensions. This result is in line with previous studies which reported the strong association between medication adherence and health literacy among older adults hypertensive patients ( 36 ) and people with hypertension ( 25 , 37 ). Baharvand et al ( 38 ) found that perceptions of illness consequences could significantly predict treatment adherence.…”
Section: Discussionsupporting
confidence: 93%
“…Um estudo realizado com 234 brasileiros diagnosticados com Hipertensão Arterial revelou que os melhores resultados de adesão ao tratamento farmacológico estiveram relacionados à maior habilidade de compreensão de orientações numéricas e de leitura (14) . Outros estudos (15)(16) evidenciam os benefícios do letramento em saúde, como uma melhora no tratamento oncológico e na tomada de decisão em pacientes com câncer de mama, além de reduzir o nível de ansiedade durante o processo.…”
Section: Introductionunclassified
“…A study conducted with 234 Brazilians diagnosed with Arterial Hypertension revealed that better results in adherence to pharmacological treatment were related to a higher ability to understand numerical instructions and reading (14) . Other studies (15)(16) highlight the benefits of health literacy, such as improvement in cancer treatment and decision-making in breast cancer patients, as well as the reduction of anxiety levels during the process.…”
Section: Introductionmentioning
confidence: 99%